2003
DOI: 10.1016/j.pbb.2003.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Altered reward value of carbohydrate snacks for female smokers withdrawn from nicotine

Abstract: Discontinuing nicotine intake usually results in weight gain partially due to heightened energy intake Iirom between-mcal snacks. This experiment tested the hypothesis that the reinforcing value of palatable carbohydrate-rich snacks increases for fernale smokers dur~ng nicotine deprivation. Eighteen smokers and 18 nonsmokers completed a concurrent-schedules operant computer task on two separate days. Sniokers were biovcrified abstinent at the second testing. The operant task allowed participants to earn points… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 65 publications
1
28
1
1
Order By: Relevance
“…Nonsmokers and smokers who are not smoking seem to perceive the sweet taste as more pleasant than smokers (62). Carbohydrate ingestion was linked to central reward centers in behavioral experiments in people undergoing nicotine withdrawal (63). Further studies involving brain imaging will be needed to elucidate the link between carbohydrate ingestion and smoking cessation.…”
Section: Appetite After Smoking Cessationmentioning
confidence: 99%
“…Nonsmokers and smokers who are not smoking seem to perceive the sweet taste as more pleasant than smokers (62). Carbohydrate ingestion was linked to central reward centers in behavioral experiments in people undergoing nicotine withdrawal (63). Further studies involving brain imaging will be needed to elucidate the link between carbohydrate ingestion and smoking cessation.…”
Section: Appetite After Smoking Cessationmentioning
confidence: 99%
“…It is also possible that rimonabant would be useful in preventing the weight gain associated with smoking cessation (Green and Harari, 1995). Increased food intake is the main factor in smoking cessation-induced weight gain (Caan et al, 1996;Eck et al, 1997;Hatsukami et al, 1993;Moffatt and Owens, 1991;Ogden, 1994;Stamford et al, 1986), but weight gain has also been related to changes in metabolic rate (Filozof et al, 2004) and to an increase in the rewarding properties of palatable foods (Lerman et al, 2004;Spring et al, 2003;Stamford et al, 1986). Chronic exposure to nicotine may induce adaptations in the brain reward system that are masked during active smoking, but induce an increase in the reinforcing properties of hedonic foods in abstinent smokers which will subsequently result in an increase in food intake and body weight gain (Bruijnzeel and Gold, 2005;Hodgkins et al, 2004).…”
Section: Combined Treatment-nicotine and Cannabinoidsmentioning
confidence: 99%
“…It is currently unknown whether smokers also show an altered brain response to palatable foods; however, in rodents, exposure to nicotine or chocolate cues elicits similar c-fos activation patterns, which are a marker of neural activation (27,28). It has also been shown that abstinent smokers display behavioral patterns that are consistent with an enhanced carbohydrate reward during performance of an operant task (29). Hence, it is possible that nicotine addiction may change the reward value of food and, thereby, influence intake.…”
Section: Introductionmentioning
confidence: 99%